2017
DOI: 10.1007/s40264-017-0527-0
|View full text |Cite
|
Sign up to set email alerts
|

Species Adulteration in the Herbal Trade: Causes, Consequences and Mitigation

Abstract: The global economy of the international trade of herbal products has been increasing by 15% annually, with the raw material for most herbal products being sourced from South and Southeast Asian countries. In India, of the 8000 species of medicinal plants harvested from the wild, approximately 960 are in the active trade. With increasing international trade in herbal medicinal products, there is also increasing concern about the widespread adulteration and species admixtures in the raw herbal trade. The adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
69
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 63 publications
0
69
0
1
Order By: Relevance
“…Globalization in the trade of herbal products and an expanding commodity market have resulted in widespread consumption of medicinal plants as drugs, cosmetics and food supplements, both in developing and developed countries 1 , 2 . Quality, safety and efficacy of herbal medicines are key requirements for public health and a major concern for regulatory authorities 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globalization in the trade of herbal products and an expanding commodity market have resulted in widespread consumption of medicinal plants as drugs, cosmetics and food supplements, both in developing and developed countries 1 , 2 . Quality, safety and efficacy of herbal medicines are key requirements for public health and a major concern for regulatory authorities 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggest that only 10% of medicinal plants traded in India are being cultivated 2 , 4 . Growing commercial demands for raw drug products increases the incentive for adulteration and substitution in the medicinal plants trade, and such adulteration can threaten consumer health, damage consumer confidence, and generally lower the trade value of such products 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Seventynine Ayurvedic herbal products were authenticated using DNA metabarcoding, and the results revealed that 67% contained a single ingredient, 21% contained multiple ingredients, and some did not contain all of the plant species mentioned on the label 15 . Much evidence supports species adulteration in herbal products, which might adversely affect consumer health and safety 6,22 . Precise and consistent sequences can be obtained for improved species determination using metabarcoding, which generates repeatable results with a reasonable cost and high-throughput sequencing 23 .…”
mentioning
confidence: 99%
“…Species substitution may adversely affect consumer health as it could cause severe allergies and will not have the intended effect (Seethapathy et al 2014;Santhosh et al 2015Santhosh et al , 2016Srirama et al 2017). Visual detection of species adulteration in the raw herbal trade is often difficult, as the plants are usually in a dry state and do not retain the original features of the plant (Seethapathy et al 2014;Santhosh et al 2015Santhosh et al , 2016.…”
mentioning
confidence: 99%
“…These results are discussed in the light of the increasing concern over safety of raw herbal drug. The need for a national regulatory mechanism that can authenticate medicinal plants used in raw trade is discussed that could offer quality assurance to customers (Srirama et al 2017).…”
mentioning
confidence: 99%